2019
DOI: 10.1002/cam4.1995
|View full text |Cite
|
Sign up to set email alerts
|

Targeting of the HER2/HER3 signaling axis overcomes ligand‐mediated resistance to trastuzumab in HER2‐positive breast cancer

Abstract: HER2‐targeted therapy, especially the anti‐HER2 antibody trastuzumab, is standard for HER2‐positive breast cancer; however, its efficacy is limited in a subpopulation of patients. HER3 ligand (heregulin)‐dependent HER2‐HER3 interactions play a critical role in the evasion of apoptosis and are therefore a target for oncotherapy to treat HER2‐positive breast cancer. The anti‐HER2 antibody pertuzumab and anti‐HER3 antibody patritumab both target this heregulin–HER3‐HER2 complex in different ways. This study exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 61 publications
(38 citation statements)
references
References 29 publications
2
36
0
Order By: Relevance
“…Additional examples, along with the wide occurrence of adaptive up-regulation of HER3 in response to stress, predict that anti-HER3 drugs might be efficacious, especially in combination with other drugs. In similarity to the study reported herein, a recent report found that triple blockade of HER2 and HER3 using two anti-HER2 antibodies and a third, an anti-HER3 mAb, could overcome resistance to trastuzumab [54], and yet another study reported that an anti-HER3 antibody can sensitize refractory NSCLC to erlotinib [55]. Hence, it is tempting to predict that HER3-targeting agents will be included in future treatment protocols.…”
Section: Discussionsupporting
confidence: 71%
“…Additional examples, along with the wide occurrence of adaptive up-regulation of HER3 in response to stress, predict that anti-HER3 drugs might be efficacious, especially in combination with other drugs. In similarity to the study reported herein, a recent report found that triple blockade of HER2 and HER3 using two anti-HER2 antibodies and a third, an anti-HER3 mAb, could overcome resistance to trastuzumab [54], and yet another study reported that an anti-HER3 antibody can sensitize refractory NSCLC to erlotinib [55]. Hence, it is tempting to predict that HER3-targeting agents will be included in future treatment protocols.…”
Section: Discussionsupporting
confidence: 71%
“…114 In addition, HER3 is an another promising strong activator of the PI3K/AKT signaling pathway, which may be upregulated after the blocking of HER2. 173…”
Section: Anti-her2-targeted Agentsmentioning
confidence: 99%
“…This association is consistent with findings for breast cancer showing that aberrant downstream signaling can give rise to resistance to HER2-targeted therapy. Heregulin serves as a ligand of HER3 and triggers HER2-HER3 heterodimerization and activation of PI3K-AKT signaling [35][36][37]. We previously found that high levels of heregulin in tumor specimens were associated with resistance to trastuzumab in both HER2-positive breast cancer and AGC [38].…”
Section: Alterations In Her2 Downstream Signalingmentioning
confidence: 99%